Proceedings of the 25th ACM SIGKDD International Conference on Knowledge Discovery &Amp; Data Mining 2019
DOI: 10.1145/3292500.3330674
|View full text |Cite
|
Sign up to set email alerts
|

Improving Subseasonal Forecasting in the Western U.S. with Machine Learning

Abstract: Water managers in the western United States (U.S.) rely on longterm forecasts of temperature and precipitation to prepare for droughts and other wet weather extremes. To improve the accuracy of these longterm forecasts, the U.S. Bureau of Reclamation and the National Oceanic and Atmospheric Administration (NOAA) launched the Subseasonal Climate Forecast Rodeo, a year-long real-time forecasting challenge in which participants aimed to skillfully predict temperature and precipitation in the western U.S. two to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 31 publications
1
88
0
Order By: Relevance
“…Obviously NGR is a simple method that uses simple predictors and assumes normality even when it is inappropriate. Some studies have demonstrated the usefulness of more advanced predictors and post-processing methods in the subseasonal-to-seasonal range (Rodney et al, 2013;Yoo et al, 2018;Hwang et al, 2019;Kämäräinen et al, 2019;Strazzo et al, 2019). Such extensions are often specific to single sources of predictability or to a fixed time aggregation.…”
Section: Statistical Post-processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously NGR is a simple method that uses simple predictors and assumes normality even when it is inappropriate. Some studies have demonstrated the usefulness of more advanced predictors and post-processing methods in the subseasonal-to-seasonal range (Rodney et al, 2013;Yoo et al, 2018;Hwang et al, 2019;Kämäräinen et al, 2019;Strazzo et al, 2019). Such extensions are often specific to single sources of predictability or to a fixed time aggregation.…”
Section: Statistical Post-processingmentioning
confidence: 99%
“…This led to noticeable increases of skill, but also to a bias for winter cold anomalies at long lead times in regions with a skewed climatological distribution (Figure 8). A correction approach that can better handle such distributions and, for example, the multiannual variability change in Iceland, might be realized with other simple (Ferrone et al, 2017;Vigaud et al, 2017) or more advanced (Yoo et al, 2018;Hwang et al, 2019;Kämäräinen et al, 2019;Strazzo et al, 2019) post-processing methods.…”
Section: F I G U R E 10 Asmentioning
confidence: 99%
“…Statistical postprocessing can be achieved through a wide range of techniques, and indeed, recent interest in climate forecast postprocessing has delved increasing into nonlinear machine learning approaches (e.g., Hwang et al 2018). We used the linear PLSR approach alluded to earlier-a components-based regression method similar to principal component regression (PCR) that combines features of principal component analysis (PCA) and multiple linear regression (Abdi 2010).…”
Section: A Partial Least Squares Regressionmentioning
confidence: 99%
“…With the development of computer science, machine learning (ML) models have begun to greatly influence many fields (Reichstein et al, 2019) and have been applied to both weather forecasting (e.g., Chattopadhyay et al, 2020;Herman & Schumacher, 2018;Weyn et al, 2019) and climate prediction (e.g., Badr et al, 2014;Chi & Kim, 2017;Cohen et al, 2019;Ham et al, 2019;Hwang et al, 2019;Iglesias et al, 2015;Kämäräinen et al, 2019;Nooteboom et al, 2018;Richman & Leslie, 2012). Some newly developed ML models show great power in improving the monthly and subseasonal forecast skills of dynamic models and may even outperform dynamic models.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nooteboom et al (2018) proposed a hybrid ML model based on an autoregressive integrated moving average (ARIMA) model and an artificial neural network (ANN) to forecast monthly ENSO indices, and this model was found to outperform the ensemble mean forecast of the Climate Forecast System version 2 (CFSv2). Hwang et al (2019) constructed two ML models and showed that the ensemble of the two ML models and CFSv2 exhibit significantly better subseasonal temperature and precipitation prediction skills over NA than the CFSv2 alone. Ham et al (2019) applied the transfer learning technique to a convolutional neural network (CNN) and showed that the CNN model outperforms the current state-of-the-art dynamic forecast system in monthly ENSO predictions.…”
Section: Introductionmentioning
confidence: 99%